Challenging and encouraging halal certification in handicraft MSMEs - Mamduh, Muhammad Faizul; Saputra, Deky Candra; Pertiwi, Soraya Noer; Widiastuti, Tika (Universitas Ahmad Dahlan, 2024)
Halal certification, a crucial aspect of the halal product industry in Indonesia, is mandatory for food and beverage products. However, awareness and understanding of halal certification remain low among Handicraft MSMEs (Micro, Small, and Medium Enterprises). This research explores the perceptions, understanding, awareness, and challenges Handicraft MSMEs face regarding halal certification. A qualitative approach with semi-structured interviews was employed as the data collection method, followed by NVivo software analysis. The results indicate that Handicraft MSMEs lack an understanding of the importance of halal certification and are unaware of the obligations and procedures involved. We identified insufficient socialization as a significant obstacle, underscoring the urgent need for more awareness campaigns and educational programs. The complexity of the certification process and lack of coordination among halal institutions are also significant obstacles. This research provides profound insights into the challenges and opportunities in implementing halal certification for Handicraft MSMEs, emphasizing the crucial role of the government in promoting and facilitating halal certification implementation for Handicraft MSMEs to support growth and competitiveness in the market. Keywords: Halal certification, Handicraft MSMEs, NVivo